2018
DOI: 10.3389/fpls.2018.01798
|View full text |Cite
|
Sign up to set email alerts
|

Root Growth, Water and Nitrogen Use Efficiencies in Winter Wheat Under Different Irrigation and Nitrogen Regimes in North China Plain

Abstract: Excessive nitrogen (N) application combined with water shortage has a negative effect on crop production, particularly wheat (Triticum aestivum L.) production in the North China Plain. This study examined root growth and water and nitrogen use efficiencies in wheat grown on loam soil in the North China Plain, from 2012 to 2014 using a fixed-position experiment initiated in 2010. The experiment followed a completely randomized split-plot design with four replications, taking irrigation [no irrigation (W0) versu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
37
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 67 publications
9
37
0
Order By: Relevance
“…While this result was based on only four lines, it could cautiously be said that selecting root dry matter at stem elongation was as good as selection at maturity. These results agree with Liu et al [40]. In a winter-wheat field experiment to evaluate the impact of N and water on root growth at multiple growth stages, they found that 71% of the variation in root weight density at maturity was explained in the variation in root weight density at jointing.…”
Section: Correlation Of Seedling and Maturity Root Phenotypes And Timsupporting
confidence: 91%
“…While this result was based on only four lines, it could cautiously be said that selecting root dry matter at stem elongation was as good as selection at maturity. These results agree with Liu et al [40]. In a winter-wheat field experiment to evaluate the impact of N and water on root growth at multiple growth stages, they found that 71% of the variation in root weight density at maturity was explained in the variation in root weight density at jointing.…”
Section: Correlation Of Seedling and Maturity Root Phenotypes And Timsupporting
confidence: 91%
“…In Trial 2, with conventional N fertilizer, significantly higher 1000-grain weights (41.56 g) and yield (5614 kg ha −1 ) were obtained in the R1 treatment (Table 2b), a result in accordance with [23] that observed a significant, positive effect of irrigation in comparison with no irrigation, in wheat grain yield and root weight density. Similar results were found by [39] when comparing two irrigation strategies with rainfed condition in winter wheat produced in the North China Plain.…”
Section: Resultssupporting
confidence: 86%
“…In fact, crop responses to N depend on available water in soil, rainfall amount, and distribution during the growth cycle [21,22]. Grain yield and N use efficiency (NUE) decrease under water deficit conditions and elevated temperatures, particularly if they occur around anthesis [16,23,24]. Nitrogen content is widely considered as the main factor that affects storage proteins and grain quality in wheat [25].…”
Section: Introductionmentioning
confidence: 99%
“…3 ), photosynthetic characteristics, and total dry biomass production. In relation to our study, recent studies also suggested that yield of several crops improved worldwide due to sustainable application of N along with appropriate management practices ( Rafiq et al, 2010 , Serrago et al, 2013 , Slafer et al, 2014 , Liu et al, 2018 ). Our finding are in consistent with ( Jeffery et al, 2006 , Gai et al, 2017 ), who reported that increase in the bulk of the grain yield of soybean crop may resulting from proper application of N fertilizer when crops needs N at suitable stage.…”
Section: Discussionsupporting
confidence: 83%